Rotary drum : fluid dynamics, dimensioning criteria, and industrial applications /: fluid dynamics, dimensioning criteria, and industrial applications. (2023) - Barrozo, Marcos A; Santos, Dyrney Araújo dos; Duarte, Cláudio Roberto; Mendonça, Suellen
No abstract available